Analisa Penjadwalan Proyek Rentang Headworks And Cipelang Main Canal Upgrading Works Rentang Irrigation Modernization Project (RIMP) Dengan Metode Diagram Pareto Kecamatan Jatitujuh Kabupaten Majalengka - Hidayat, Agus; Nurjamilah, Lia Lailla; Taruan, Erni Sari Lombun (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2023)
Project scheduling has an important role in ensuring smooth project implementation and achieving the desired project objectives. In this context, the project scheduling analysis of the Rentang Headworks and Cipelang Main Canal Upgrading Works Rentang Irrigation Modernization Project (RIMP) in Jatitujuh District, Majalengka Regency is important to ensure the efficiency and effectiveness of project implementation. The Pareto diagram method is used in this analysis to identify and address key issues that may arise during project implementation. This research aims to improve the scheduling of the RIMP project by using the Pareto diagram method to increase the efficiency of time, cost, and resources. The results of the analysis show that the critical factors affecting the scheduling of the RIMP project are delays in material procurement, lack of coordination between related parties, and changes in demand from stakeholders. In the Pareto diagram, these problems are placed on the Y-axis and ranked in order of importance. After identifying the main problems, specific improvement measures were proposed to address each problem. Measures such as improving material procurement, enhancing coordination between relevant parties, and devising a more structured change request mechanism can help reduce delays and improve project scheduling efficiency. Using the Pareto diagram method, this RIMP project scheduling analysis provides a clear view of the key issues affecting project execution. The results of this analysis can be used by the project team to make better decisions in project planning and execution, with the hope of improving the efficiency and success of the project.